Gating by induced Α–Γ asynchrony in selective attention. Issue 10 (24th May 2018) - Pascucci, David; Hervais‐Adelman, Alexis; Plomp, Gijs
Abstract: Visual selective attention operates through top–down mechanisms of signal enhancement and suppression, mediated by α‐band oscillations. The effects of such top–down signals on local processing in primary visual cortex (V1) remain poorly understood. In this work, we characterize the interplay between large‐scale interactions and local activity changes in V1 that orchestrates selective attention, using Granger‐causality and phase‐amplitude coupling (PAC) analysis of EEG source signals. The task required participants to either attend to or ignore oriented gratings. Results from time‐varying, directed connectivity analysis revealed frequency‐specific effects of attentional selection: bottom–up γ‐band influences from visual areas increased rapidly in response to attended stimuli while distributed top–down α‐band influences originated from parietal cortex in response to ignored stimuli. Importantly, the results revealed a critical interplay between top–down parietal signals and α–γ PAC in visual areas. Parietal α‐band influences disrupted the α–γ coupling in visual cortex, which in turn reduced the amount of γ‐band outflow from visual areas. Our results are a first demonstration of how directed interactions affect cross‐frequency coupling in downstream areas depending on task demands. These findings suggest that parietal cortex realizes selective attention by disrupting cross‐frequency coupling at target regions, which prevents them from propagating task‐irrelevant information.